Self-esteem and mathematics learning. 5th grade secondary students. IE 5166 Beautiful Aurora. Puente Piedra, Lima - Vivar Gonzalez, Julio Arnulfo (2023)
Self-esteem is one of the most important ingredients in the achievement of learning in regular basic education, especially in adolescents, and the objective of this study is to establish if there is a relationship between self-esteem and the ability to learn mathematics in 5th grade students. secondary school, for which we use scientific research with a quantitative approach, hypothetical deductive method, cross section and ordinal level. A descriptive correlational design allows us to develop a questionnaire survey with Likert-type questions validated by expert judgment and reliability through Cronbach's alpha statistician. The non-probabilistic sample made up of 40 5th year high school students from school 5166 Bella Aurora, was measured through descriptive statisticians and for the hypothesis test using Spearman's Rho for the variables: self-esteem and mathematics learning in which obtained an r=0.690, with a significance of 0.000 lower than the decision made of 0.05, allowing us to reject the null hypothesis and accept the alternative that says that there is a high significance between self-esteem and mathematics learning, manifesting their dependence functional.